PEMBELAJARAN KIMIA DENGAN PENDEKATAN STEM (SCIENCE, TECHNOLOGY, ENGENEERING, AND MATHEMATICS) SEBAGAI UPAYA MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA : SYSTEMATIC LITERATURE REVIEW - Rahmah Zalianti, Suci; Heriana Putri, Adia; Siska, Novia; Rifa Audina, Dian (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Critical thinking is a skill that students must possess in 21st-century learning, particularly in chemistry education. This study aims to analyze the application of the STEM approach to enhance students’ critical thinking skills in chemistry education. The research method used is a Systematic Literature Review. The Systematic Literature Review method consists of three stages: planning, implementation, and reporting. The planning stage involves determining the topic, formulating the research question, and establishing criteria for the articles to be used as references. The implementation stage involves conducting the systematic literature review, and the reporting stage involves writing the systematic literature review article. The systematic literature review was conducted on articles aligned with the study’s objectives. Articles were obtained using SciSpace and Google Scholar and selected based on criteria from Sinta S2–S6 published between 2019 and 2024. The review of these articles identified fourteen articles that met the research criteria, and their quality was assessed. The research findings conclude that the application of the STEM approach can enhance students’ critical thinking skills in chemistry learning.